Seasonal Predictions of Holopelagic Sargassum Across the Tropical Atlantic Accounting for Uncertainty in Drivers and Processes: The SARTRAC Ensemble Forecast System - Marsh, Robert; Addo, Kwasi Appeaning; Jayson-Quashigah, Philip-Neri; Oxenford, Hazel A.; Maxam, Ava; Anderson, Romario; Skliris, Nikolaos; Dash, Jadu; Tompkins, Emma L. (Frontiers in Marine Science, 2021)
The holopelagic macroalgae sargassum has proliferated across the tropical Atlantic since 2011, of consequence for coastal populations from West Africa to the Caribbean with limited early warning of major beaching events. As part of an interdisciplinary project, ‘Teleconnected SARgassum risks across the Atlantic: building capacity for TRansformational Adaptation in the Caribbean and West Africa’ (SARTRAC), an ensemble forecast system, SARTRAC-EFS, is providing seasonal predictions of sargassum drift. An eddy-resolving ocean model hindcast provides the winds and currents necessary to generate ensemble members. Ensemble forecasts are then obtained for different combinations of ‘windage’, the fractional influence of winds on sargassum mats, and in situ rates of growth, mortality, and sinking. Forecasts for north and south of Jamaica are evaluated with satellite-observed distributions, associated with beaching events in specific years of heavy inundation, 2015 and 2018-20. These seasonal forecasts are evaluated, on lead times of up to 180 days. Forecasts are subject to leading modes of tropical climate variability, in particular the Atlantic Meridional Mode (AMM). More accurate forecasts for a given year are obtained with ensemble members from hindcast years with a similar spring AMM-index. This is most clearly evident during negative AMM phases in spring of 2015 and 2018, when positive sea surface temperature anomalies and anomalously weak trade winds were established across the northern tropics. On this evidence, SARTRAC-EFS is potentially useful in providing early warning of high sargassum prevalence. Extended to sargassum drift off West Africa, extensive cloud cover limits availability of the satellite data needed for full application and evaluation of SARTRAC-EFS in this region, although experimental forecasts off the coast of Ghana are found highly sensitive to the windage that is associated with strong onshore winds during boreal summer. Alongside other forecast systems, SARTRAC-EFS is providing useful early warnings of sargassum inundation at seasonal timescale.